Comparison of Social, Economic and Familial Empowerment in Married Women in Three Cities of Iran - Masoumeh Simbar; Shiva Alizadeh; Mahboubeh Hajifoghaha; Fatemeh Dabiri (Shiraz University of Medical Sciences, 2017)
Background: Women's empowerment was defined as their ability to achieve awareness and control their personal, social, economic and political forces aiming at taking measures in order to improve their lives. This study aimed to compare the empowerment of the married women in medical sciences university in social, economic and familial domains in three cities, IRAN. Methods: This was a descriptive-analytical study conducted in 2016 on 399 married and employed women. Data collection instrument was a four-part questionnaire consisting of demographic, social, economic and familial domains and made by researchers. Collected data were analyzed using SPSS, version 16. Using paired t-test for intra-group and Chi-square and t-test for between groups comparisons. The significance level was set at<0.05. Results: The total score of empowerment in Rasht (126.34±17.51) was more than the two cities of Shiraz (123.46±15.62) and Bandar Abbas (123.42±12.34). There was a significant relationship between the mean score of the total empowerment and monthly income of the participants in Bandar Abbas (P=0.04), and job of their husbands in Rasht (P=0.004). The mean score of family empowerment of the women was significantly interrelated with the number of their children in Rasht (P=0.001), and with the education of the participants' husbands in Shiraz (P=0.002). Conclusion: The score of social empowerment in Rasht was more than two other cities. In economic domain, the scores of Rasht and Bandar Abbas were more than those of Shiraz. Scores of Rasht and Shiraz were more than Bandar Abbas in the familial domain. It is useful to carry out qualitative studies aiming at determining the effects of various factors on women's empowerment and strategies for improving it..